2013
DOI: 10.1002/gps.3930
|View full text |Cite
|
Sign up to set email alerts
|

White matter fractional anisotropy is inversely related to anxious symptoms in older adults with atherosclerosis

Abstract: Objective Clinical anxiety disorders are associated with white matter hyperintensities and diffusion abnormalities measured using diffusion tensor imaging (DTI). However, it is not known if this association extends into individuals with mild anxious symptoms without formal diagnosis, in those who are older, or in those who have atherosclerosis. The current study explored whether white matter integrity and/or organization significantly associates with anxious symptoms in older adults with and without atheroscle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 51 publications
0
10
0
1
Order By: Relevance
“…The associations observed with higher MD and lower FA, generally reflective of decreases in fiber integrity and brain connectivity, suggests cerebral microstructural differences exist in type 2 diabetes with anxiety and depression. A previous analysis of older adults with atherosclerosis found reduced WMFA in those with increased anxiety (Bijanki, Stillman et al 2013), and differences in white matter microstructure, as reflected in FA and MD measures, have also been reported in late-life depression (Shimony, Sheline et al 2009). Reductions in GMV have been observed in late life depression (Sexton, Mackay et al 2013) as well as anxiety (Moon, Kim et al 2014).…”
Section: Discussionmentioning
confidence: 89%
“…The associations observed with higher MD and lower FA, generally reflective of decreases in fiber integrity and brain connectivity, suggests cerebral microstructural differences exist in type 2 diabetes with anxiety and depression. A previous analysis of older adults with atherosclerosis found reduced WMFA in those with increased anxiety (Bijanki, Stillman et al 2013), and differences in white matter microstructure, as reflected in FA and MD measures, have also been reported in late-life depression (Shimony, Sheline et al 2009). Reductions in GMV have been observed in late life depression (Sexton, Mackay et al 2013) as well as anxiety (Moon, Kim et al 2014).…”
Section: Discussionmentioning
confidence: 89%
“…The SCL-90-R Depression Scale has shown strong correlation with the Beck Depression Inventory ( Beck et al, 1988 ), suggesting convergent validity ( Steer et al, 1994 ). Previous analysis by our group has shown that scores on the SCL-90-R are suitably sensitive to show relationships with brain structural measures ( Bijanki et al, 2013b ). In the parent study of 111 AVD and 51 HC participants, the AVD participants had significantly elevated SCL-90-R depression scores compared with the HC participants (AVD mean 55.18, HC mean 50.67, t = 2.466, df = 160, p = 0.015), supporting the premise that AVD participants experience elevated levels of depressive symptoms.…”
Section: Methodsmentioning
confidence: 98%
“…Presence of anxiety symptoms was defined by a positive response to any of the following questions: “In the past month, have you felt anxious or frightened?”; “Were there times lately that you felt anxious?”; “Are there special situations that make you anxious?”; and “Have you ever had attacks of fear or panic?”. Presence of anxiety symptoms is a potential confounder, because anxiety symptoms are frequently present in individuals with depression, and are associated with cerebrovascular disease independently of depression (27, 28). Gait speed, a measure of physical performance (29), was the time needed to walk 6 meters at a usual pace.…”
Section: Methodsmentioning
confidence: 99%